Waste to fuel: A detailed combustion, performance, and emission characteristics of a CI engine fuelled with sustainable fish waste management augmentation with alcohols and nanoparticles - Sathish, T.; Agbulut, Umit; Ubaidullah, Mohd; Saravanan, R.; Giri, Jayant; Shaikh, Shoyebmohamad F. (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
All over the world, 130 million tonnes of fish waste have been generated per annum. Improper disposal of such waste leads to environmental pollution, habitat degradation, oxygen depletion, spread of pathogens, parasites, and diseases. From this point of view, this research motivated to benefit from such fish waste by converting an alternative fuel along with various additives for diesel engines. Fish wastes gathered from the fish market are used as feedstock for producing fish waste biodiesel (FWBD) through the transesterification process. The derived fish waste biodiesel (FWBD) 60 %, 20 % diesel, and 20 % n-butanol (C4H9OH) by volume were blended (60FWBD+20Bu+20D) to form the test fuels. Then the fuel blends were used to convert two nano fuels by separately adding zinc oxide and graphene nanoparticles of 100 ppm along with sodium dodecyl sulphate surfactant, and the nanoparticles-added test fuels were exposed to sound waves of 50 kHz in an ultrasonicator for 1 h. These fuels were characterized to derive and ensure the fuel properties for diesel engines and tested such fuels in a 5.2 kW CI engine to do a comparative study. The experiments were conducted at the constant engine speed of 1500 rpm, and varying engine loads from 25 % to 100 % with intervals of 25 %. When the fish waste biodiesel was added to diesel fuel, the engine performance worsened in a given engine load, but it started to improve with the existence of nanoparticles. Compared to 60FWBD+20Bu+20D, graphene-based nano fuel blend recorded 1.99 % higher BTE, but 15.03 % higher NOx. Similarly, compared to 60FWBD+20Bu+20D, zinc oxide-based nano fuel blends recorded 6.75 % higher BTE and reduced NOx, CO, HC, and smoke emissions by 29.97 %, 15.98 %, 22.0 %, and 16.03 % respectively. In conclusion, the present research reveals that fish wastes can be used in diesel engines without any modification on the vehicular system, and this may contribute to both slowing down the rate of depletion of fossil reserves and the waste management of the fish wastes from nature in a useful way.
Keywords: Waste to energy; Fish waste oil biodiesel; Nano fuel; Zinc oxide; Graphene; Engine emission; OIL; Thermodynamics; Energy & Fuels